Educação integral e justiça curricular: Projeto Escola Trabalho de Confecção em São Bernardo do Campo (2011-2016) - Siraque, Terezinha Cristina Nakamatsu (2022)
Through the analysis of a Vocational Education experience that occurred in São Bernardo do Campo (2011-2016), state of São Paulo, Brazil, with the Projeto Escola Trabalho de Confecção [Clothing Manufacturing School Project], this research presents the possibility of conducting a citizen Vocational Education. In the analysis, it is highlighted, in addition to the technical training for work, strictly understood in the sense of the immediate training of women for the labor market, that this experience brought, in its curriculum, principles of Integral Education and Curricular Justice. It has as theoretical support Freire (1987, 2011), Torres Santomé (2013a), Ponce (2018), Ponce and Araújo (2019) in the discussion about the critical curriculum and Curricular Justice; Arroyo (2012a) contributes to the analysis of impoverished groups, the profile of the subjects served, the curriculum as a disputed territory and with the concept of Integral Education; Paro (2013), Ciavatta and Ramos (2012) and Frigotto, Ciavatta and Ramos (2012) point out reflections on labor in its ontological sense; Cunha (2005a, 2005b) and Manfredi (2002) discuss the history of Vocational Education; Moll (2012), Teixeira (1975), Mascellani (2010) and Silva (2016) bring the theme of Integral Education; Santos (2018, 2019) assists with his concept of Epistemologies of the South; and finally, Bardin (2016) gives support to the Content Analysis made from the results of the searches performed. The qualitative approach research was conducted with semi-structured interviews, questionnaires and reports of students, graduate students, administration managers and education professionals who participated in the construction of the project and the production and analysis of documents at the time (2011 to 2016). The data collected are appreciated from the perspective of Integral Education; of the three dimensions of Curricular Justice: knowledge, coexistence and care; of the concept of Epistemologies of the South; and from the Content Analysis. The study aims to contribute to the reflections on critical and emancipatory Vocational Education